DIKSI SEKSUALITAS DALAM NOVEL TRILOGI RONGGENG DUKUH PARUK KARYA AHMAD TOHARI - Sarjono (BASTRA : Jurnal Penelitian Pendidikan Bahasa dan Sastra, 2017)
This study was conducted with the aim to describe the meaning of sexuality diction contained in the trilogy novel of Ronggeng Dukuh Paruk by Ahmad Tohari. Data were collected by using a technique of library, seeing and recording. The collected data was then analyzed using flow analysis consisting of three flow of activities occured simultaneously, namely data reduction, data presentation, and drawing conclusions. The results showed that there are 11 (eleven) diction concerning sexuality in the trilogy novel of Ronggeng Dukuh Paruk by Ahmad Tohari, namely (a) bukak-klambu, (b) virginitas, (c) tonggak sejarah biologis, (d) mucikari atau induk semang, (e) dengus napas lembu jantan, (f) sundal/persundalan, (g) lingga, (h) rajasinga, (i) gendak, (j) pacak gulu, and (k) gowok.